Analisis Efektivitas Pembelajaran Creative Problem Solving dalam Meningkatkan Kreativitas Berpikir dan Kemampuan Komunikasi Peserta Didik pada Mata Pelajaran Geografi Kelas X IPS SMAN 1 Kartasura - Anisatun Nuzula Fitriani; Sugiyanto Sugiyanto; Sarwono Sarwono (Universitas Sebelas Maret (UNS), 2025)
This study aims to examine the differences in effectiveness between the Creative Problem Solving learning model and the expository learning model in improving students' creative thinking skills and communication skills in Geography subjects for class X IPS at SMA Negeri 1 Kartasura in the 2021/2022 academic year. The method used is a quasi-experiment with data analysis techniques including normality tests, variance homogeneity tests, Mann-Whitney tests, and N-Gain Score calculations to determine the level of effectiveness of each model. Based on the results of the analysis, it was found that the application of the Creative Problem Solving model was more effective in improving students' creative thinking skills than the expository model, as evidenced by the results of the Mann-Whitney test.